Pengaruh penggunaan media korong hitung terhadap kemampuan pemecahan masalah operasi hitung perkalian siswa Kelas II SD Muhammadiyah Klepu - Saputro, Hengkang Bara; Hidayati , Annisa Nur (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This study aims to determine the effect of funnel box media (KORONG) arithmetic on the problem solving ability of multiplication arithmetic operations of second grade students at SD Muhammadiyah Klepu. This research uses pre-experimental designs with a quantitative approach. The research design uses one group pretest-posttest. The population of this study were all students of class II, totaling 13 students. The sample of this research uses saturated sampling technique. The instruments used were observation sheets and test questions. Data analysis technique using paired sample t-test with a significance level of 5%. Based on the results of the t test, it shows that the value (Sig) is 0.000 <0.05 and the value (-7.298) < (2.179) which means that is accepted and is rejected. So, it can be concluded that there is an influence between the use of funnel box media (KORONG) arithmetic on the problem-solving ability of multiplication arithmetic operations of class II SD Muhammadiyah Klepu